2014
DOI: 10.1039/c4ra03178d
|View full text |Cite
|
Sign up to set email alerts
|

pH-dependent cross-linking of catechols through oxidation via Fe3+and potential implications for mussel adhesion

Abstract: The mussel byssus is a remarkable attachment structure that is formed by injection molding and rapid in-situ hardening of concentrated solutions of proteins enriched in the catecholic amino acid 3,4-dihydroxy-L-phenylalanine (DOPA). Fe3+, found in high concentrations in the byssus, has been speculated to participate in redox reactions with DOPA that lead to protein polymerization, however direct evidence to support this hypothesis has been lacking. Using small molecule catechols, DOPA-containing peptides, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
107
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 45 publications
1
107
0
Order By: Relevance
“…Fe(III)-dependent dimer formation decreases with increasing pH. Dimerization occurs most readily at pH 2, can be detected at pH 5, and is absent at pH 7 and 9, where Fe(III) coordination is favored over Fe(III) induced oxidation [86]. A Dopa autoxidation product was observed at pH 9 in the absence of Fe(III) and this product is not detected in the presence of Fe(III), demonstrating that Fe(III) coordination protects Dopa against autoxidation [86].…”
Section: Oxidation Of Catechols By Fe(iii) In Mussel Plaquesmentioning
confidence: 96%
See 2 more Smart Citations
“…Fe(III)-dependent dimer formation decreases with increasing pH. Dimerization occurs most readily at pH 2, can be detected at pH 5, and is absent at pH 7 and 9, where Fe(III) coordination is favored over Fe(III) induced oxidation [86]. A Dopa autoxidation product was observed at pH 9 in the absence of Fe(III) and this product is not detected in the presence of Fe(III), demonstrating that Fe(III) coordination protects Dopa against autoxidation [86].…”
Section: Oxidation Of Catechols By Fe(iii) In Mussel Plaquesmentioning
confidence: 96%
“…. Dopa-containing small molecules and model peptides also form covalently crosslinked aryl dimers at pH 2 in the presence of Fe(III) [86]. Fe(III)-dependent dimer formation decreases with increasing pH.…”
Section: Oxidation Of Catechols By Fe(iii) In Mussel Plaquesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, spectroscopic evidence has linked the presence of Fe 3+ to catechol oxidation for decades [16] [17] [18]. It has been reported that catecholmodified polyethylene glycol (PEG) polymers could be covalently cross-linked under acidic pH conditions in the presence of Fe 3+ [19] [20]. Therefore, the mechanism of interactions between Fe 3+ and catechols must be extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…An inexpensive and biocompatible self-healing hydrogel for injectable cell therapy carrier was also investigated by Yang et al [14]. Recently, some significant work has focused on non-covalent hydrogels, which are cross-linked by reversible interactions based on metal-ligand coordination in the polymer chains; these can provide stimuli responsiveness, magnetic self-healing and good mechanical properties [8][9][10][15][16][17][18][19][20]. Because of the thermodynamics and kinetic properties of metal-ligand coordination bonds, metal-ligand interactions can provide stable, reversible crosslinking points between polymers [21].…”
Section: Introductionmentioning
confidence: 99%